Soil exchangeable cations and acidity components in different cropping systems for onion (JOURNAL OF ADVANCES IN AGRICULTURE, 2022)
This study aimed to evaluate K, Ca, Mg, Al concentrations and active acidity (pH-H2O) in different cropping systems for onion. The study was conducted on a Humic Dystrudept in Ituporanga, Santa Catarina state, Brazil, where eight different cropping systems for onion were evaluated, namely: T1: maize-onion succession, T2: common vetch-maize/rye+fodder raddish-onion-maize/rye+fodder raddish-common bean, T3: rye-onion-maize/black oat-maize, T4: onion-velvet bean succession, T5: rye-onion-millet/black oat-onion-millet, T6: rye-onion-velvet bean succession, T7: onion-velvet bean+millet+sunflower succession, from T1 to T7 were conducted under no tillage system (NTS), T8, T8: maize-onion succession, was conducted under conventional tillage system. We used the randomized complete block design, with 5 replications. All the chemical samples were collected and evaluated at the 0-5, 5-10 and 10-20 cm soil layers. We observed that the different cropping systems were similar in terms of Ca, Mg and K concentrations in all the soil layers, significant differences were only found for exchangeable Al concentrations at the 0-5 cm layer. More time is needed to observe better the performance of the treatments since their effect on the soil depends a lot on the time of implantation.